THE DATABASE OF PEDAGOGICAL TERMS AS A PEDAGOGICAL TECHNOLOGY IN MULTILINGUAL EDUCATION - T.A. Kudelko (Многоязычие в образовательном пространстве)
This article describes innovative pedagogical technologies in multilingual education. The author considers the relevance of multilingual education in the modern world, the theoretical foundations of multilingualism and pedagogical technologies for teaching multilingual students. The compilation and description of the database of pedagogical terms is presented by the author as one of the innovative pedagogical technologies in the educational multilingual process. The author considers the theoretical base of terminology and compiling a database of terms. The article proposes a methodology for studying terms in the pedagogical industry to compile a database in several languages by students from Russia and Turkmenistan (Russian, English, German, Turkmen languages). The advantages of working with google tables are revealed, as this contributes to the development of the skill of multilingual communication competence. The Results section presents practical examples of students’ work with pedagogical terms, including different types of linguistic analysis. The steps of the table are described down to examples with explanations. This technology was successfully tested in English classes at the University (Perm) with students of the pedagogical direction. The resulting database was recommended for registration in the All-Russian database.